The Impact of Political Connections, Transfer Pricing, and Corporate Governance on Tax Avoidance - Al Falah, Faiq Taj; Barli, Harry; Irawati, Wiwit (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2025)
This study aims to analyse the influence of political connections, transfer pricing, and corporate governance, represented by managerial ownership, institutional ownership, and an independent board of commissioners, on tax avoidance. The population of this study consists of coal sector mining companies listed on the Indonesia Stock Exchange between 2018 and 2022. This study applied a quantitative method with a purposive sampling technique, involving a population of 41 companies, and produced 8 company samples. The results of this study show that political connections affect tax avoidance, while transfer pricing, managerial ownership, institutional ownership, and an independent board of commissioners have no partial effect on tax avoidance. Simultaneously, all independent variables affect tax avoidance